2020
DOI: 10.31599/jies.v1i2.320
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Perbaikan Kualitas Pelayanan Menggunakan Metode Quality Function Deployment (Studi Kasus Cafe XYZ Rawalumbu)

Abstract: ABSTRACT Culinary business in Bekasi is growing more and more, both cafes or other fast food restaurants. This encourages entrepreneurs, investors to do culinary business. One of the fast food culinary businesses is the XYZ cafe. This study discusses the analysis of service quality in XYZ cafe about voice of customers to increase customer satisfaction at XYZ cafe. The purpose of this study is to determine the priority scale to increase the customers satisfaction based on the voice of customer and know wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In this research, the method used is Quality Function Deployment (QFD) which is then processed using the House of Quality (HoQ) method. Several stages in the Quality Function Deployment analysis are determining customer quality criteria, determining company aspects, determining score weights, determining relative importance rankings, determining critical incidents, determining competitive benchmarks, determining linkage networks with a scale ratio of 9 : 3 : 1 [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the method used is Quality Function Deployment (QFD) which is then processed using the House of Quality (HoQ) method. Several stages in the Quality Function Deployment analysis are determining customer quality criteria, determining company aspects, determining score weights, determining relative importance rankings, determining critical incidents, determining competitive benchmarks, determining linkage networks with a scale ratio of 9 : 3 : 1 [4].…”
Section: Methodsmentioning
confidence: 99%
“…Some of them are the discovery of dumplings with different levels of maturity and changing tastes of dumplings. Thus, the company certainly wants to provide the best for its customers by correcting deficiencies in its products [4]- [6]. To help find out how to improve product quality according to consumer needs and expectations, an analytical tool is used in the form of a Quality Function Deployment (QFD) in the form of a House of Quality (HoQ) [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…If r counts > 0.1966, then the variable relationship is significant, but if r counts < 0.1966, then the variable relationship is not significant. A research questionnaire can be said to be reliable if the answers from respondents to the questionnaire statement are consistent over time (Prasmoro et al, 2020). This test uses the SPSS 24 application using the Cronbach alpha formula of 0.6.…”
Section: Attributementioning
confidence: 99%
“…The third priority is to Organize regular evaluations of employee service performance (score 27) research conducted by (Santi &;Isyanto, 2023) states that by conducting evaluations or performance appraisals employees can evaluate employee competencies as a whole, including their advantages and disadvantages, to help optimal job position placement. In research conducted by (Prasmoro et al, 2020) it has been found that there needs to be a thorough evaluation of the state of the Cafe. Technical response, which is a top priority, should immediately find the right solution for the company and employees to meet consumer needs.…”
Section: Figure 1 Hoq Middle Roommentioning
confidence: 99%
“…4. Menentukan Matriks Korelasi (Correlation Matrix) & Relationship MatrixMatriks Korelasi merupakan hubungan antara respon teknis satu dengan respon teknis yang lainnya.Sedangkan Relationship Matrix merupakan hubungan antara respon teknis dengan atribut pelayanan[14].Gambar 3: Matriks Korelasi (Correlation Matrix) &Relationship Matrix Gambar 4: Lanjutan Matriks Korelasi (Correlation Matrix) &Relationship MatrixBerdasarkan Gambar 3 dan 4 diketahui untuk hubungan setiap respon teknis satu dengan respon teknis yang lainnya. Kemudian diketahui juga untuk atribut pernyataan dengan respon teknis ada yang memiliki hubungan kuat dan ada juga yang tidak memiliki hubungan.5.…”
unclassified